2007
DOI: 10.1016/j.aquaculture.2006.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein level on growth and energy utilization by Litopenaeus stylirostris under laboratory conditions

Abstract: A study was conducted using a bioenergetics approach to generate information on energy requirement and feed utilization of Litopenaeus stylirostris. Animals (initial mean weight 21 ± 1 g were fed ad libitum six experimental diets, ranging from 25 to 58% crude protein (CP), for 50 days.Weight gain increased from 21 to 30 g with increasing dietary protein level. Survival rates averaged 80%. Basal metabolism (HeE) and heat increment of feeding (HiE) were monitored using respirometry. HeE was on average 1 kJ shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…Gaylord et al (2002) reported that the reduction of dietary crude protein from 30 to 25% with or without 0.5% L-lyisne.HCl reduced channel catfish production, moreover, supplemental lysine provided no additional benefits in terms of yield or water quality. In this study, the FCR, PER, and feed intake were not affected by the dietary protein level, which is highly consistent with reports on Nile tilapia (Botaro et al 2007), but different from the study on Litopanaues stylirostris (Gauquelin et al 2007). The results of digestibility study exhibited that shrimps fed low crude protein and fish meal diets supplementation of synthetic AA (diets 2-4) digested crude protein and other nutrients just as good as those fed the normal diet, which confirmed the results obtained from feeding trial.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gaylord et al (2002) reported that the reduction of dietary crude protein from 30 to 25% with or without 0.5% L-lyisne.HCl reduced channel catfish production, moreover, supplemental lysine provided no additional benefits in terms of yield or water quality. In this study, the FCR, PER, and feed intake were not affected by the dietary protein level, which is highly consistent with reports on Nile tilapia (Botaro et al 2007), but different from the study on Litopanaues stylirostris (Gauquelin et al 2007). The results of digestibility study exhibited that shrimps fed low crude protein and fish meal diets supplementation of synthetic AA (diets 2-4) digested crude protein and other nutrients just as good as those fed the normal diet, which confirmed the results obtained from feeding trial.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, there is a general agreement in the literature that reducing CP concentration by 2-3% with CAA inclusion does not reduce growth performance of growing and finishing pigs (Tuitoek et al 1997;Liu et al 1999;Otto et al 2003;Kerr et al 2003). In contrast, Gauquelin et al (2007) found that the weight gain of Litopanaues stylirostris decreased linearly with CP level reduction from 58 to 25%. Gaylord et al (2002) reported that the reduction of dietary crude protein from 30 to 25% with or without 0.5% L-lyisne.HCl reduced channel catfish production, moreover, supplemental lysine provided no additional benefits in terms of yield or water quality.…”
Section: Discussionmentioning
confidence: 76%
“…The allocation of energy toward different physiological functions may vary due to ontogenetic stage, sex, age, diet, salinity, temperature, or eyestalk ablation [M. rosenbergii (Nelson & Knight 1977;Sierra & Diaz 1999), L. vannamei (Pascual et al 2004), L. stylirostris (Gauquelin et al 2007), C. parallelus (Rocha et al 2013)]. …”
Section: Energy Budgetmentioning
confidence: 99%
“…Although the number of studies utilising this approach is still limited, in recent years there has been an increasing interest in this topic (e.g. Arnould et al, 2005;Eder & Lewis, 2005;Doyle et al, 2007;Gauquelin et al, 2007;Tang et al, 2007;Di Beneditto et al, 2009;Spitz et al, 2010;Hossain et al, 2011).…”
Section: Introductionmentioning
confidence: 99%